Don't look back - Armentrout, Jennifer L. (Hyperion, 2015)
Seventeen-year-old Sam seems to have everything until she and her best friend, Cassie, disappear one night and now Sam has returned with amnesia, striving to be a much better person and aware that her not remembering may be the only thing keeping Sam alive.